The Impact of Sentencing on Offenders' Future Labour Market Outcomes and Re-offending- Community Work Versus Fines - Michele Morris; Charles Sullivan (New Zealand Government, The Treasury, 2015)
This study provides evidence to help inform sentencing policy by assessing the differential impact of two types of sentences (community work and fines) on adult offenders subsequent employment, benefit receipt and re-offending. This is the first study in New Zealand to examine post-sentencing employment outcomes and benefit receipt of such offenders. We focus on offences where we observe variation in sentencing after controlling for observable differences and examine outcomes for up to three years following conviction. This analysis uses recently-linked anonymised administrative data from the tax, benefit and justice systems within Statistics New Zealand's Integrated Data Infrastructure, which provides detailed information on all convicted offenders and their offending. Impacts are estimated by comparing the changes in post-conviction outcomes of offenders who received a fine with changes in outcomes for matched comparison groups of offenders who received a community work sentence. Matching is done using the method of propensity score matching. Impacts are estimated separately for four types of offences and for a general model that pools several types of offences together. People sentenced to community work are more likely to re-offend within two years of conviction compared to fined offenders. There is no difference in impact on employment during the follow-up period for the two types of sentences (except in one case where there is a short-term differential impact in the year following conviction). We find that people sentenced to community work are more likely to be on benefit following conviction compared to people who are fined. We regard our estimates as an upper bound of the true differential impact of community work compared to fines on offenders' subsequent outcomes. While our method controls for observed offender characteristics, it is still possible that there are significant uncontrolled differences between the offenders who were sentenced to community work and those who were fined (eg, the differences in being on benefit could be due to differences in the level of financial support from a partner).
Keywords: K14; D04; 330; Strafe; Erwerbstätigkeit; Arbeitsmarktintegration; Straftäter; Neuseeland